Optimizing Marketing Strategy through SWOT Analysis in Sales Increase at PT Arhapro - Hironimus Hilapok (Return : Study of Management, Economic and Bussines, 2025)
In the era of the industrial revolution, 4.0 has opened up opportunities and challenges in increasingly fierce competition between companies in the same industry. Companies are required to utilize various effective strategies to increase sales results. This study aims to look at the application of SWOT analysis in building a marketing strategy that is expected to increase sales results at PT Arhapro. The method used is qualitative, with data obtained through interviews and literature studies. The results showed that the application of SWOT analysis was carried out through several stages, namely the identification of the company's internal strengths and weaknesses and opportunities and threats from the external environment. Through the analysis, researchers found that PT Arhapro's strengths lie in product quality and a loyal customer base, while its weaknesses include limitations in promotion. From the external side, the opportunities that can be utilized are the increasing market demand, while the threats come from aggressive competitors. The implication of this research is that SWOT analysis not only strengthens the theory but can be used as a practical guide for companies that can be applied by marketing practitioners in facing various increasingly modern market dynamics. Further research is needed with a wider sample and with more varied methods to deepen the understanding and application of SWOT analysis in various industrial contexts and market dynamics.